STUDY OF THE KINETICS AND MECHANISM OF PHENYLDIETHA-NOLAMINE-POTASSIUM PERSULFATE REACTION IN WATER. II. THE REGULARITIES OF THE ACCUMULATION OF THE COLOURED PRODUCT AND THE INFLUENCE OF BASE AND ACID ON THE REACTION RATE (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The kinetics of the accumulation of a coloured product, as well as the influence of base and acid additions on the phenyldiethanolamine-potassium persulfate reaction rate in water at 298 K have been studied. It has been established that the addition of H2SO4 slows down the reaction, which is result of amine's molecule binding to the corresponding salt. The base's action nature on the rate of the studied reaction differs from cases described in literature concerning amine-peroxide reactions. The obtained data are explained assuming that in presence of NaOH the nature of formed aminyl radicals is changed. It means that NaOH changes the mechanism of phenyldiethanolamine's oxidation by persulfate.